Sustainability of Anshun Dixi opera as an intangible cultural heritage from the ecosystem of music perspective - Heng, Wu; Chiat, Loo Fung; Jan, Chan Cheong (Human Resources Management Academic Research Society (HRMARS), 2024)
This study presents the effort to employ the music ecosystem model in assessing the sustainability of Chinese music traditions in the context of preserving worldwide musical variety and safeguarding intangible heritage. The research focuses on the Chinese traditional opera Anshun Dixi as the subject of investigation, intending to examine the impact of sociocultural elements on its sustainability. It features conversations on the sustainability of Anshun Dixi by 16 culture bearers from 9 Tunpu villages based on an ecosystem of music. The research results further validate important evaluation indicators that influence the sustainability of Anshun Dixi, including financial support issues, a lack of career opportunities, a lack of cohesive development models within the community, and the performance system’s reliance on informal means of transmission. Furthermore, the music ecosystem model exhibits connections among its five domains (learning systems, musicians and communities, contexts and constructures, infrastructure and regulations, media and the music industry), forming a complex and interconnected network.